TRADITIONAL SINGING: ROOTS OF UZBEK MUSICAL CULTURE (Web of Teachers: Inderscience Research, 2025)
This scientific article explores the formation, historical evolution, and current state of traditional Uzbek vocal art. It examines major regional performance schools — Bukhara, Fergana-Tashkent, and Khorezm — analyzing their stylistic characteristics. The study also investigates the connection between vocal performance and maqom music, the role of the master-apprentice system, and the contribution of female singers. Traditional singing is presented as a core component of the national musical identity and intangible cultural heritage of Uzbekistan.